'And part not with my revelations for a trifling price': Reconceptualizing Islam's Aniconism through the lenses of reification and representation as meaning-making. (March 2020) - Kaminski, Joseph J
This article contends that Islamic prohibitions on certain types of figural imagery serve a dual function. In addition to fulfilling their traditional Islamic role related to preserving Allah's sovereignty, such prohibitions also facilitate in preventing Islam's essential message from being transformed via crass and sentimentalist reproductions of its most sacred symbols and figures. The article first defines the term 'icon' and then engages with the more recent discourse surrounding representation as meaning-making. It then connects Islamic aniconism to Marxist and post-structuralist concerns related to reification, commodification, and the transformation of sacred symbols into forms of personal property. The final part of this article engages with the rulings of Yusuf al-Qaradawi and Taha Jabir al-Alwani regarding figural imagery to show that these prohibitions are not absolute and that there are varying degrees of acceptability based on form, content, and purpose.